Peri-Conceptional undernutrition in twin bearing ewes: Effect on early fetal growth and birth weight - Vicente-Pérez, Ricardo; Osorio-Marín, Yolanda; López-Baca, María de los Angeles; Avendaño-Reyes, Leonel; Correa-Calderón, Abelardo; Mellado, Miguel; Lara-Rivera, Ana L.; Meza-Herrera, Cesar A.; Macias-Cruz, Ulises (Ecosistemas y Recursos Agropecuarios, 2017)
A total of 48 Katahdin x Pelibuey multiparous ewes were used to evaluate the e ect of nutritional restriction (40 %) before (30 d, RT), after (50 d, TR) or both periods (80 d, RR) compared with a control group on maternal body status, early fetal growth and lamb birth weights. Only twin bearing ewes were selected at d 50 of pregnancy for fetal measurements by ultrasonography and record of birth weight. Compared with control ewes, lower (p < 0.05) weight and body condition score had RT and RR ewes at mating time, likewise, TR and RR ewes at d 50 post-conception. There were mainly di erences between fetuses from control and RT ewes, being higher (p < 0.05) the vesicular, abdominal and fetal area, as well as crown-rump length and birth weight for RT fetuses. In conclusion, preconception undernutrition positively altered the early fetal growth and lamb birth weights in hair ewes pregnant with twins.